Recommending a Patient-Level Study to Confirm that BCG Vaccination Accounts for the Relatively Low COVID-19 Mortality Rate in the Philippines - Azcarraga, Amulfo P. (Animo Repository, 2020)
Medical researchers have pointed out wide differences in COVID-related death rates among countries; and several explanations have been offered such as the high number of old people in a country, number of tourists, number of immigrants, geographic location and climate, size of the population, etc. One possible explanation that deserves further study is that countries where the COVID death rate is low are those countries where mass BCG vaccination is in place, such as the Philippines. Indeed, compared to countries who have never had mass BCG vaccination, i.e. USA, Canada, Italy, Netherlands and Belgium, the death rate due to COVID-19 in the Philippines is 16 to 131 times lower. The difference is also quite large compared to those countries where there had been mass BCG vaccination in the past but had been discontinued for two to four decades.